Rodeo Athletes' Perceptions of the Available Onsite Medical Care Provided - Rachel Kesterson; Erika Smith-Goodwin; Jennifer Walker; Perry Denehy (Journal of Sports Medicine and Allied Health Sciences: Official Journal of the Ohio Athletic Trainers' Association, 2022)
OBJECTIVE: The purpose of this study was to investigate the medical care perceptions of rodeo athletes at one Southwest Ohio rodeo as compared to others. MAIN.OUTCOME.MEASURE: The survey was made of 23 Likert-scale questions.